Functional parameters, wrist posture deviations and comfort: A comparison between a computer mouse and a touch pen as input devices. - Hemati, Karim; Mirjalili, Sedigheh; Ghasemi, Mohamad Sadegh; Abdolahian, Yeganeh; Siroos, Razeyeh; Sanati, Pardis; Aghilinejad, Mashallah; Dehghan, Naser (Work, 2020)
BACKGROUND: Performing common computer tasks such as pointing, clicking, and dragging requires repetitive movements that cause musculoskeletal disorders in the wrists and hands. Given the growing use of touch screens and touch pens, further studies on the ergonomics of these devices are needed. This study aimed to compare a touch pen and an ordinary computer mouse in terms of movement time, error rate, wrist posture, and comfort of use. METHODS: Performance parameters (movement time and error rate), wrist postures, and comfort when using a mouse and a touch pen were measured based on ISO 9241-9 standard with the help of 27 participants. For data analysis, paired t test was performed using SPSS version 22. RESULTS: Using the touch pen resulted in better performance parameters than using the mouse (p < 0.05). Wrist extension and flexion were lower when performing the task with the computer mouse than with the touch pen (p < 0.05). When using the touch pen to perform the task, ulnar deviation and radial deviation were lower (p < 0.05). The overall comfort was higher when using the mouse than the touch pen. CONCLUSION: Our results showed that the touch pen had better performance parameters than the ordinary mouse and also resulted in lower ulnar and radial deviations. Given the impact of habit and proficiency on users' comfort in using input devices, it is reasonable to expect users becoming more comfortable by using touch pens on the long term.